FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENERAPAN STRUKTUR PENGENDALIAN INTERN LEMBAGA PERKREDITAN DESA - Pratiwi, Ade Ayu Cahyaning; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
The aim of this study is to get empirical evidence about the effect of independence, motivation, education level and working experience of the internal controllers on the effectiveness of the internal control structure LPD in Badung distric. Sample determine by probability sampling method use cluster sampling which obtained 55 units sample with 110 people of internal control. Multiple linear regression analysis is use to analyzed the data. The results of this analysis are motivation give positive effect on the effectiveness of the internal control structure. The education give positive effect on the effectiveness of the internal control structure. Work experience give positive effect on the effectiveness of the internal control structure. The independence has no effect on the effectiveness of the internal control structure.
Keywords: independence, motivation, education, effectiveness, control